2022
DOI: 10.3389/fonc.2021.811434
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Hyaluronan on Tumor Progression in Cutaneous Melanoma

Abstract: The incidence of cutaneous melanoma is rapidly increasing worldwide. Cutaneous melanoma is an aggressive type of skin cancer, which originates from malignant transformation of pigment producing melanocytes. The main risk factor for melanoma is ultraviolet (UV) radiation, and thus it often arises from highly sun-exposed skin areas and is characterized by a high mutational burden. In addition to melanoma-associated mutations such as BRAF, NRAS, PTEN and cell cycle regulators, the expansion of melanoma is affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 206 publications
(245 reference statements)
0
4
0
Order By: Relevance
“…Similar structures were not found in M0 or M2 CM-exposed cells. Previous studies have shown a protective role of pericellular HA against extrinsic factors, such as UVR and chemotherapeutic drugs (Ha sova ´et al, 2011;Takabe et al, 2022;Va ´radi et al, 2012). In melanocytes, the pericellular HA coat has been shown to protect against UVB-induced inflammatory responses (Takabe et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…Similar structures were not found in M0 or M2 CM-exposed cells. Previous studies have shown a protective role of pericellular HA against extrinsic factors, such as UVR and chemotherapeutic drugs (Ha sova ´et al, 2011;Takabe et al, 2022;Va ´radi et al, 2012). In melanocytes, the pericellular HA coat has been shown to protect against UVB-induced inflammatory responses (Takabe et al, 2019).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, platelet-derived growth factor β and transforming growth factor have been found to be the only growth factors that have been shown to prevent the mesothelioma growth. Despite the reality that various growth factors and even their receptors play a role in the dissemination of mesothelioma ( 25 ).…”
Section: Pathogenesismentioning
confidence: 99%
“…Among all the matrix components, HA is one of the most deregulated in human malignancies, and its amount in the tumor stroma affects overall survival and outcome [37][38][39]. High levels of HA are observed in several tumors compared to healthy tissues, such as renal [40], hepatocellular [41], head and neck [42] and lung squamous cell carcinomas [43], lymphoma [44], glioma [45], prostate [46], melanoma [47], breast [48], and ovarian [49] cancers. In most cancer cases, stromal accumulation of HA strongly correlates with an unfavorable prognosis and decreased survival probability [37,49,50].…”
Section: The Role Of Ha In Tumor Stromamentioning
confidence: 99%